(untitled) (Stato, Chiese e pluralismo confessionale, 2020)
SUMMARY: 1. Scholar challenges and epistemological pitfalls - 2. Traditional Muslim hermeneutics and the development of schools of Jurisprudence - 3. Jurist’s authority and ruler’s governance from a comparative perspective - 4. Muslim legal tradition of plural jurisdictions - 5. The open scholar question of reciprocal legal influences with other juridical systems - 6. Conclusive remarks. ABSTRACT: This article analyzes several open scholar debates regarding the Muslim legal system, from the conventional narrative of its formation and the triumph of the Traditionalist movement to the disputed question of reciprocal legal influences with other religious and secular juridical systems. This research tries to avoid two epistemological risks: first, the dangers of a simplistic binary debate like traditionalists v. revisionists, religious v. secular, or even Sunnis v. Shiite reducing the analysis to an ideologically polarized and ineffective dispute; and second, the improper use of juridical neologisms applied to the Islamic legal system, mainly from codified European continental law and English common law as a result of the Orientalist, colonialist, and secularist mentalities that, instead clarification create confusion. From a hermeneutical point of view, two characteristics to keep in mind: 1) the notion of divine law and its legal implications; and 2) the relationship between law and theology that is not correlative to the connection between secular legislation and ideology. From a comparative point of view, three challenging questions to address: 1) the distinction between Usul al-fiqh and Usul al-qanun often blurred in practice showing the complexities of the relationship among religious, legal, and political structures under Muslim ruling; 2) the intertwined relationship among Sharia, fiqh, and siyasa with pre-Islamic administrative, legal, and judicial traditions; 3) Jurisdictional pluralism in the Islamic legal practice concerning non-Muslim minorities.